ANAlLISIS AlGEN SERUMENOLITIK CUKAl AlPEL 2,5% DAlN MINYAlK KELAlPAl PAlDAl AlNAlK PAlNTI AlSUHAlN PUTRI AlISYIYAlH KOTAl MEDAlN SECAlRAl IN VITRO - NATASYA, SAVIRA AYU; SIREGAR, SITI MASLINA (LP2MTBM MAKARIOZ, 2023)
Cerumen impalction can occur in all ages, including children, adults, and the elderly, which is influenced by dangerous falctors.Cerumenolytic algents can soften and dissolve alcohol, one of which is almond vinegar (2.5% and Coconut Oil is also used asallternaltives. The aim of this study is to evaluate the effectiveness of cerumenolitic alginate Alpple Cider Vinegar 2.5%Coconut Oil as an alternative therapy for the prevention of cerumen in children of the Puteri Alisyiyalh Orphalnalge in Medaln Cityin vitro for 5, 10, 15, and 30 minutes. Type This study is an in vitro laboratory study using a UV-Vis spectrophotometer.simple random sampling technique. The result of this research are The mealn ralnk vallue for the effect of Alpple Cider Vinegal.2.5% is 32.40, while coconut oil is 16.60. In addition, a P-value of 0.000 wals was obtained; this value is <0.005 so itcould be stalled because there is always a difference in the solubility of cerumen. Which mealns the effect of Alpple Vinegar 2.5% isgrealter thaln coconut oil. Based on the results of the research that has been done, it can be concluded that giving AlphaCider Vinegalr2.5% as a serumenolytic alginate will be effective alfter use in the 15th minute. The use of coconut oil did nothalve significant effectiveness algalinst cerumen impalction theralpy in vitro for the 5th, 10th, 15th, and 30th minutes. Alpple CiderVinegalr 2.5% has better effectiveness in terms of solubility. cerumen by showing a higher average value of Coconut oil.early time of the experiment.